Supercritical fluid extraction from Lippia alba: global yields, kinetic data, and extract chemical composition - Braga, MEM; Ehlert, PAD; Ming, Lin Chau [UNESP]; Meireles, MAA (Elsevier B.V., 2005)
In this work, experimental data for the system Lippia alba + CO2 is presented. The major constituents of the L. alba volatile oil are limonene and carvone. Thus, literature data for the systems limonene + CO2 and carvone + CO2, and the Peng-Robinson equation of state (PR-EOS) were used to select the operating temperature and pressure, which maximize the global yield in L. alba extract. Global yields were determined at 80, 100, and 120 bar and 40, 45, and 50 degrees C. L. alba extracts were also obtained by conventional processes (hydrodistillation, low-pressure ethanol extraction and Soxhlet ethanol). The chemical compositions of the extracts were determined by gas and thin layer chromatography (TLC). The secretor structures of L. alba were observed by scanning electron microscopy (SEM) before and after supercritical extraction. The largest yield (similar to 7%, mass of extract/mass of dry solid) of the CO2-extract was obtained at 318 K and 100 bar. The chemical compositions of the CO2-extracts were different from those of the extracts obtained by Soxhlet and low-pressure solvent extraction (LPSE) because of the co-extraction of heavy substances by ethanol. The operating conditions that maximized the carvone and limomene yields were 80 bar and 323 K (80 mass%) and 120 bar and 323 K (17 mass%), respectively. (c) 2004 Elsevier B.V All rights reserved.
Keywords: carvone; extraction kinetics; phase equilibrium; limonene; Lippia alba; supercritical fluid extraction